Enhancing the Amino Acid and Reducing the Metal Ions Contents in the Hydrolysate Resulting from Hydrothermal Carbonization of Chicken Feather Waste by Chemical Phosphorylation - Agus Kuncaka; Wahyu Tri Supardi; Winarto Haryadi; Adhitasari Suratman; Priatmoko Priatmoko (Indonesian Journal of Chemistry, 2023)
Chemical phosphorylation of hydrolysate resulting from hydrothermal carbonization of chicken feather waste was performed to enhance the amino acids and reduce the metal ions content. The aim of this research is to improve the functional properties of chicken feathers hydrolysate without impairing the nutritional availability thereof with the cheapest chemical method by phosphorylation. Phosphorylated hydrolysate can function as animal feed and fertilizer. The hydrolysate of chicken feathers was obtained by hydrothermal carbonization in an alkaline condition using a CaO and KOH catalyst, by the ratio of water:dry matter of chicken feathers is 5:1, at 9–10 atm pressure, and in a temperature of 190–200 °C during 3 h. Phosphorylation has been carried out by reacting the hydrolysate with H3PO4 85% in pH of 5, 6, 7 and using the original hydrolysate as control. The sample that has been prepared was characterized and semi-quantitative analyzed by HPLC and AAS. The phosphorylation results showed that the total maximum protein of soluble protein, their minimum metal ions, and anion in soluble protein was obtained at pH 7, while the higher the pH, the lower the liquid protein that was obtained.